(untitled) (Pakistan Journal of Engineering, Technology and Science, 2025)
This study provides the design, development, and functional characterization of a new affordable transradial myoelectric prosthesis, specifically designed to tackle the twin challenges of affordability and functional complexity that restrict the availability of commercial prosthetic systems. The overall goal of this work is to develop a completely open-source, anthropometrically optimized, and cost-effective prosthetic platform that facilitates natural motor control with surface electromyography (sEMG) signals from the remaining limb. The design presented utilizes an optimized signal acquisition and decoding architecture that is capable of converting sEMG activity to real-time proportional control commands. The methodological process includes multi-step signal processing, such as acquisition from cutaneous electrodes, analog conditioning, digital decoding using an Arduino Uno microcontroller, and actuation using a five-servo array controlled by a PCA9685 driver. All structural elements, such as the socket and hand structure, were produced using additive manufacturing and dimensionally tested with anthropometric specifications to provide ergonomic comfort and functional stability. Experimental testing ensured an 18 dB enhancement in Signal-to-Noise Ratio (SNR), a mean response time of 210 ± 30 milliseconds, and a static load capacity of 1.8 kg, indicating strong electronic integrity and useful usability for everyday tasks. The overall cost of fabrication, quantified as around USD 65, reflects unparalleled economic viability. Overall, this study sets a significant milestone towards affordable bionic technology with an open-source, high-utility prosthetic system that has the potential to span the gap between performance and price in upper-limb rehabilitation